The m-CMP Inverse in Minkowski Space (Communications in Mathematical Research, 2024)
In this paper, a new generalized m-CMP inverse is introduced intothe Minkowski space, and its related properties are discussed. Secondly, threedifferent expressions of m-CMP inverse are listed, namely Hartwig-Spindelböck decomposition, full-rank decomposition and integral expression. Finally,the application of the inverse m-CMP equation in solving linear equations isgiven.